Debt conservatism in shipping: determinants and investment implications - Gulnur, Arman (Routledge Journals, Taylor & Francis Ltd, 2026)
The shipping industry exhibits an observable presence of firms that operate with zero-leverage, despite being a capital-intensive and traditionally debt-reliant sector. From 1995 to 2020, an average of 20 shipping companies maintained a zero-leverage policy annually, diverging from the industry's standard reliance on debt. This study investigates the determinants and investment implications of zero-leverage policies in the shipping industry. An analysis of 5,666 firm-year observations reveals that most zero-leverage shipping firms are financially constrained, while a smaller subset avoids debt to preserve financial flexibility. Companies with no debt are generally smaller, possess fewer tangible assets, and distribute higher dividends. Notably, shipping companies reduce investment by an average of $41.3 million in the year they adopt zero-leverage, yet investment rises by $43.6 million in the subsequent years upon reintroducing debt. After an extended zero-leverage period, companies that reintroduce debt achieve higher investment levels. Limited debt capacity is common among zero-leverage firms, with financially stronger firms raising more debt upon reintroduction, further enhancing investment. This study offers deeper insights into zero-leverage behaviours in the shipping industry, characterised by unique operational dynamics.
Keywords: Debt conservatism; shipping industry; zero leverage; capital structure